Resposta da mamoneira a lâminas de irrigação, ao número de dias com irrigação e a aplicação de nitrogênio - Moreira, Levi Gonçalves (2008)
With the objective of evaluating the answers of the mamoneira to different irrigation sheets, to numbers of days with irrigation and the application of nitrogen in argisolo red-yellow, three experiments were installed, in the municipal district of Fortaleza-CE. In all of the experiments, the sowing was made in holes, spaced of 1,0 x 1,0 m. The experimental delineamentos were in blocks casualizados with 5 treatments and 4 repetitions for each experiment. In the first experiment was tested five laminate of irrigation: 25, 50, 75, 100 and 125 of ECA. In the second experiment different numbers of days were evaluated with irrigation, where the treatments consisted of irrigating up to the 75; 90; 105; 120 and 135 days after the germination (DAG). The third experiment aimed at to evaluate the effects of growing doses of nitrogen, applied he/she saw fertirrigação. The treatments they constituted of: 0, 50, 100, 150, and 200% of nitrogen starting from the recommendation of the soil analysis. They were appraised the productive factors of the culture as: numbers of fruits for racemo, weight of 100 seeds and productivity of the racemos of 1st, 2nd and 3rd orders, and total productivity. The data were submitted to the variance analysis and later when significant for the test F at the level of 1 or 5% of probability, were submitted to regression analyses, being looked for to adjust equations with biological meanings. The software was used "SAEG 9.0. UFV." In the first experiment it is ended that the irrigation with a sheet de1.310mm (103,8% of the evaporation measured in the tank class "THE"), provided the largest productivity 4.129kg.ha -1. In the second experiment the obtained results demonstrate that when it was irrigated until the 105 days after the germination happened the largest total productivity with value of 2.833kg.ha -1. The third party the experiment it is ended that the applied dose of nitrogen saw fertirrigação of 131% of the it recommends for the it analyzes of soil was the one that provided better total productivity of 3.640,9kg.ha -1.